2017
DOI: 10.1016/j.eururo.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell Sequencing Reveals Variants in ARID1A, GPRC5A and MLL2 Driving Self-renewal of Human Bladder Cancer Stem Cells

Abstract: Human bladder cancer stem cells show the high level of consistency and may derived from bladder epithelial stem cells or bladder cancer non-stem cells. Mutations of ARID1A, GPRC5A and MLL2 grant bladder cancer non-stem cells the capability of self-renewal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 9 publications
2
86
0
1
Order By: Relevance
“…There may be multiple molecular subtypes in the same tumor, which may be an important factor affecting the accuracy of the molecular subtyping prediction system. With the rapid development of single-cell high-throughput sequencing (46,55,56), mass spectrometric detection (57), immune analysis (58,59), and other technologies, the accuracy of the molecular subtyping prediction system will be further improved (Figure 4). Compared with traditional pathological classification, molecular subtyping offers a more comprehensive analysis of the genome, transcriptome and non-coding RNA, providing important guidance for BC adjuvant chemotherapy, targeted therapy and immunotherapy.…”
Section: Mibc Molecular Subtypingmentioning
confidence: 99%
“…There may be multiple molecular subtypes in the same tumor, which may be an important factor affecting the accuracy of the molecular subtyping prediction system. With the rapid development of single-cell high-throughput sequencing (46,55,56), mass spectrometric detection (57), immune analysis (58,59), and other technologies, the accuracy of the molecular subtyping prediction system will be further improved (Figure 4). Compared with traditional pathological classification, molecular subtyping offers a more comprehensive analysis of the genome, transcriptome and non-coding RNA, providing important guidance for BC adjuvant chemotherapy, targeted therapy and immunotherapy.…”
Section: Mibc Molecular Subtypingmentioning
confidence: 99%
“…Little overlapping of somatic exonic mutations existed between the two cancers showing the normal urothelial stem cell origin [5]. The authors did not address how their findings could reconcile with recent data from mouse lineage tracing suggesting divergent progenitor cells for bladder cancer variants [6] (and see below).…”
mentioning
confidence: 86%
“…In addition, the authors identified 21 mutated genes in bladder cancer stem cells, of which six were novel. Finally, the authors demonstrated that mutation of ARID1A, GPRC5A, and MLL2 all together, but not singly or in various combinations, conferred stem-cell characteristics to bladder cancer non-stem cells [5].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The methylation of histone H3K4me3, and the expression of downstream GATA4 , ETS1 were enhanced significantly in recurrent BC tissues and patients with higher expression of GATA4 and ETS1 has a shorter survival time, which revealed that H3K4me3 and the expression of GATA4 and ETS1 were promising targets for monitoring and treatment of BC recurrence . Yang et al identified 21 key altered genes in BCSCs including five novel mutated genes ( GPRC5A, MKL1, PAWR, PITX2, and RGS9BP ) in BC by single‐cell sequencing, and found that the co‐mutations of ARIDA1, GPRC5A, and MLL2 played a critical role in maintaining the stemness of bladder cancer stem cells . Above results provided more possibilities for the targeted therapy of BC.…”
Section: Research Front Of Precision Diagnosis In Bladder Cancermentioning
confidence: 99%